Accumulation of 131I in Esophageal Diverticulum Diagnosed by SPECT/CT. (November 2018) - Rizzo, Alessio; Zagaria, Luca; Perotti, Germano; Annunziata, Salvatore; Salvatori, Massimo
Abstract : Abstract: A 72-year-old man underwent total thyroidectomy and radioiodine remnant ablation for papillary thyroid cancer in 2016. The posttherapy whole-body scan showed uptake in the neck, classified as residual thyroid tissue. Two years later, the patient came to our observation to perform a second radioiodine therapy for high levels of thyroglobulin. The planar posttherapy scan showed a focal radioiodine area in the neck. SPECT/CT diagnosed a voluminous esophageal diverticulum located in the upper third of the esophagus. A CT performed to discover the source of thyroglobulin excluded locoregional or distant metastases and confirmed the presence of a Zenker diverticulum.